Targeting SHP2 as a promising strategy for cancer immunotherapy. (February 2020) - Liu, Qianqian; Qu, Jiao; Zhao, Mingxia; Xu, Qiang; Sun, Yang
Graphical abstract: Targeting SHP2 plays multiple roles in cancer. ① SHP2 is a critical regulator of RAS-MAPK pathway. SHP2i may inhibit cancers driven by RTK or KRAS alteration. ② SHP2 is a critical downstream effector for PD-1/PD-L1 and CD28 pathway. SHP2i may facilitate CD8 + cytotoxic activity. ③ SHP2 is a critical downstream effector for M-CSF/CSF-1R pathway. SHP2i may suppress the activities of TAM. In general, SHP2 inhibitors might target cancer cell, T lymphocyte and macrophage simultaneously, thereby exerting strong anti-tumor effects. Abstract: Src homology-2-containing protein tyrosine phosphatase 2 (SHP2) is a major phosphatase involved in several cellular processes. In recent years, SHP2 has been the focus of significant attention in human diseases, particular in cancer. Several studies have shown that SHP2 plays an important role in regulating immune cell functions in tumor microenvironment. A few clinical trials conducted using SHP2 allosteric inhibitors have shown remarkable anti-tumor benefits and good safety profiles. This review focuses on the current understanding of the regulation of SHP2 and highlights the vital roles of SHP2 in T lymphocytes, macrophages and cancer cells. It also summarizes the current development of SHP2 inhibitors as a promising strategy for cancer immunotherapy.